Nominalisasi, Abstraksi Makna dan Metafora Gramatikal dalam Terjemahan Surah Al-Fatihah: Nominalization, Abstraction of Meaning and Grammatical Metaphor in the Translation of Surah Al-Fatihah - Siregar, Usmala Dewi; Nasution, Meisa Fitri; Febriani, Budi (Information Technology and Science(ITScience), 2025)
Surah Al-Fatiha, as the opening chapter of the Qur'an, holds a significant position in Islamic teachings because it contains profound theological, spiritual, and linguistic values. Translating Surah Al-Fatiha into other languages ??often results in changes in lexical and grammatical structures that impact shifts in meaning. The primary challenge in translating religious texts lies in striking a balance between the literal accuracy of the text and the depth of its spiritual message. This study aims to analyze the processes of nominalization, meaning abstraction, and grammatical metaphors that appear in the translation of Surah Al-Fatiha using the Systemic Functional Linguistics (Halliday) framework. The research method employed is a descriptive qualitative approach, involving the steps of identification, classification, and interpretation of the forms of nominalization and grammatical metaphors in the Indonesian translation text. The results show that the first five verses of Surah Al-Fatiha contain various forms of nominalization, such as